APLIKASI METODE PANGKAT DALAM MENGAPROKSIMASI NILAI EIGEN KOMPLEKS PADA MATRIKS - Novita Eka Chandra; Wiwin Kusniati (Unisda Journal of Mathematics and Computer Science (UJMC), 2016)
Power method is a method of iterations to nd the eigenvalues in the matrix. Based on previous research has been conducted to nd of application thepower method eigenvalues in the matrix. However, in these studies is limited to real eigenvalues . In this study , power method applied to nd the complex eigenvalues of a matrix . With the help of Matlab program in accordance with the results obtained using the results of manual workmanship . From the results, it can be conclusion that the power method can be applied to nd the complex eigenvalues in a matrix.